The Reversed Canvas: A Topos of Conflict Between Commercial and Aesthetic Values in Nineteenth-Century Paris and London - Richard Read (Sillages Critiques)
This chapter concerns the double valency of commercial and aesthetic values in reversed paintings depicted in nineteenth-century French and British paintings and cartoons of academic juries. My concern is not with actual backs of paintings, but with representations of them on the rectos of actual paintings, of which the best-known example is probably the huge canvas back in Diego Velázquez’s Las Meninas (1656). Likewise, my concern is not with the frame itself, but with intra-compositional frames of paintings (which I sometimes call versos or “backs”) depicted on the picture plane. Though the topos makes us aware that the painting we are looking at has a frame (which we can see) and a verso (which we cannot), I shall show how, especially when depicted on the move in outdoor settings, the reversed canvas embedded in the illusion may alert us to “extended” or “secondary frames” well outside its enframed setting, such as the studio where the painting was made or the gallery it will hang in or the jury room from which it has been rejected. In this respect the commercial and aesthetic meanings richly associated with the topos merge, intermingle and define each other in ways that illuminate polemical clashes of value in and between places of display in nineteenth-century London and Paris.